2014
DOI: 10.1007/s11102-014-0585-6
|View full text |Cite|
|
Sign up to set email alerts
|

Pasireotide LAR maintains inhibition of GH and IGF-1 in patients with acromegaly for up to 25 months: results from the blinded extension phase of a randomized, double-blind, multicenter, Phase III study

Abstract: PurposeA large, randomized, double-blind, Phase III core study demonstrated that pasireotide LAR was significantly superior to octreotide LAR at providing GH <2.5 μg/L and normalized IGF-1 after 12 months’ treatment in patients with acromegaly. We report the efficacy and safety of pasireotide LAR and octreotide LAR after up to 26 months’ treatment.MethodsPatients with GH <2.5 μg/L and IGF-1 ≤1× ULN at month 12, or patients considered to be experiencing clinical benefit, were eligible to continue receiving thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 19 publications
9
67
0
Order By: Relevance
“…Although there were differences between the current study design and the 2 multinational phase 3 studies, the response rates in the subgroups: SSA uncontrolled, n=20: ~10.0% to 20.0% and others/SSA naïve, n=13: ~15.4% to 30.8% (range based on values at different time points) were consistent with the response rates observed in these 2 phase 3 studies for patients with inadequately controlled acromegaly [16] and patients with treatment-naïve acromegaly [14], respectively. A more pronounced reduction of median percentage change from baseline in standardized IGF-1 was observed in others/SSA-naïve group when compared to SSA-uncontrolled group at month 12, whereas median percentage change from baseline in mean GH was similar in both the groups.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although there were differences between the current study design and the 2 multinational phase 3 studies, the response rates in the subgroups: SSA uncontrolled, n=20: ~10.0% to 20.0% and others/SSA naïve, n=13: ~15.4% to 30.8% (range based on values at different time points) were consistent with the response rates observed in these 2 phase 3 studies for patients with inadequately controlled acromegaly [16] and patients with treatment-naïve acromegaly [14], respectively. A more pronounced reduction of median percentage change from baseline in standardized IGF-1 was observed in others/SSA-naïve group when compared to SSA-uncontrolled group at month 12, whereas median percentage change from baseline in mean GH was similar in both the groups.…”
Section: Discussionsupporting
confidence: 77%
“…Somatostatin subtype receptors (SSTRs), especially 2 and 5, are found to be prevalent on GH-secreting pituitary adenomas [4]. Octreotide and lanreotide, the first-generation SSAs, which similar to other SSAs except for a higher frequency and degree of hyperglycemia [14][15][16]. Long-acting pasireotide is approved for the treatment of acromegaly by the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) [17,18], and in many other countries based on results of these 2 pivotal trials.…”
mentioning
confidence: 99%
“…An increase in the dose of sitagliptin and metformin was needed to maintain glycemic control after 24 months of treatment. As was recently reported in the C2305 25-month extension study, metformin was the most commonly used antidiabetic medication for managing pasireotide-induced hyperglycemia (10). Thus, the patient in the current study was able to remain on therapy with sustained control of IGF-1 and clinical symptoms.…”
Section: Discussionsupporting
confidence: 61%
“…7,8 A phase 3 core study by Sheppard et al found that more patients with normal fasting plasma glucose (FPG)(<100mg/dL) at baseline developed hyperglycemia at their final assessment on pasireotide compared with octreotide (69% vs 39%). 9 Treatment options have been proposed. A phase 1 study by Breitschaft et al, 8 co-administered pasireotide along with an anti-hyperglycemic to healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%